The effect of different processing, injection molding (IM) and fused deposition modeling (FDM), on the environmental stress cracking (ESC) behavior of filled and unfilled polycarbonate (PC) - M. Z. Huang; J. Nomai; A. K. Schlarb (eXPRESS Polymer Letters)
The effect of crack propagation management by using a fused deposition modeling (FDM) technique on the environmental stress cracking (ESC) behavior of neat polycarbonate (PC) and PC with 1 vol% SiO2 nanocomposites were investigated. The results demonstrate that the crack growth behavior of materials and their ESC resistance are strongly dependent on the printing direction. The ESC resistance and failure time of an FDM print-on injection-molded specimen exhibit the greatest values when the printing direction parallels to the load direction. Comparative analyses of the fracture surfaces reveal that the excellent stress cracking resistance can contribute to favorable stress and load distribution at the crack front area, where the printed continuous strands in alignment with the load can efficiently carry and transfer it. However, the degree of ESC improvement by managing the direction of craze/crack propagation via printing direction is more pronounced in neat PC than those of PC-SiO2 nanocomposites.